The Effect of Buriti Oil (Mauritia flexuosa L.) as Feed Additive on the Organic and Inorganic Materials Digestibility on Heat Stress Exposed Broilers - Burhanudin; Sunaryo Hadi Warsito; Bodhi Agustono; Nusdianto Triakoso; Ragil Angga Prastiya; Faisal Fikri (Universitas Airlangga, 2024)
Heat stress due to high environmental conditions can affect the digestibility of organic and inorganic broilers. Buriti oil (Mauritia flexuosa L.) contains antioxidants that can suppress Reactive Oxygen Species (ROS) thereby reducing the negative effects of heat stress. This study aims to determine the effect of adding buriti oil to the ration on the organic and inorganic matter of digestibility in broiler exposed to heat stress. This research was experimental and the method used is the completely randomized design method (CRD). The treatment be carried out on 20 broiler aged 22-35 days who are kept in individual cages. Broiler in the treatment group were given heat stress induction using gasolec up to a temperature 35 ± 1o°C for 4 hours every day. Broiler were randomly selected in 4 treatment groups divided into K- (temperature 27 ± 2°C + complete feed), K+ (exposure to temperature 35 ± 1°C + complete feed), P1 (exposure to temperature 35 ± 1°C + complete feed + 2% buriti oil total feed gram /head /day) and P2 (exposure to temperature 35 ± 1°C + complete feed + 4% buriti oil total feed gram /head /day).